Ice speed skating: Onset of lubrication by frictional heating - van Dongen, M. E. H.; Smeulders, D. M. J. (Europhysics Letters, 2021)
In ice speed skating, the friction between the steel skate blade and the ice stems from boundary friction where the temperature of the interface is below zero and ice surface molecules exhibit unconventional mobility, and hydrodynamic friction where the ice melts and a thin water layer between the blade and the ice forms. An analytical solution of the steady-state lubrication equation shows that the boundary friction only plays a role at the tip of the skate blade over an extremely short contact length between the skate blade and the ice. Albeit its negligible contribution to total friction, boundary friction generates enough heat to melt the ice which allows the skater to slide smoothly on a thin layer of melt water. It is also shown that the precise value of the boundary friction coefficient is not important for speed skate friction because it works only over an extremely short contact length.